Issues in corporate governance and finance - Hirschey, Mark; John, Kose; Makhija, Anil K. (Emerald, 2007)
While Advances continues to publish papers from any area of Finance, the focus of this issue is on corporate governance, broadly defined as the system of controls that helps corporations and other organizations effectively manage, administer, and direct economic resources. Papers of this title deal with the role played by boards of directors, impact of ownership, executive compensation, and investor protection. Other papers deal with stock repurchases, default, banking, financial sector development, and the Asian financial crisis. Papers cover a wide range of international experience, including evidence from the U.S., Japan, Israel, Malaysia, China, and New Zealand. Papers cover a wide range of international experience with this issue focusing on corporate governance. This book series is available electronically at website.
Keywords: Corporate governance.; elektronické knihy; electronic books